Laboratory study of subjective perceptions to low temperature heating systems with exhaust ventilation in Nordic countries. (3rd April 2017) - Jin, Quan; Simone, Angela; Olesen, Bjarne W.; Holmberg, Sture K.M.; Bourdakis, Eleftherios
Abstract : Given the global trends of rising energy demand and the increasing utilization of low-grade renewable energy, low-temperature heating systems can play key roles in improving building energy efficiency while providing a comfortable indoor environment. To meet the need to retrofit existing buildings in Nordic countries for greater energy efficiency, this study focused on human subjects' thermal sensation, thermal comfort, thermal acceptability, draft acceptability, and perceived air quality when three low-temperature heating systems were used: conventional radiator, ventilation radiator, or floor heating with exhaust ventilation. Human subject tests were carried out in the climate chamber at the Technical University of Denmark. In total, 24 human subjects, 12 females and 12 males, participated in the tests during the winter season. The results show that no significant differences in thermal sensation and thermal comfort between the three heating systems. Ventilation radiator promised a comfortable indoor environment with a decreased water supply temperature and floor heating with exhaust ventilation can provide a basic thermal comfort level. Thermal acceptability and draft acceptability show variations in different heating systems. Gender has significant influences on thermal sensation, draft acceptability, and preference of clo values. Personal thermal preference is observed between males and females. The males prefer to dress lighter than the females, but both can get the same thermal comfort level. It is concluded that low-temperature heating systems using exhaust air ventilation are a potentially solution when buildings are being retrofitted for improved energy efficiency and comfort of the occupants.